1998
DOI: 10.1111/j.1151-2916.1998.tb02407.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Enhanced Reactivity of Silicon for the Formation of Silicon Nitride Composites

Abstract: The chemical reactivity of silicon can be enhanced by mechanical activation. Ball milling elemental silicon powders with a small amount of carbon addition at ambient temperature has resulted in an enhanced nitridation of silicon at high temperatures. In comparison with powder mixtures without milling, the nitridation process at 1250°C has been accelerated by a factor of 9 and 23 by milling powder mixtures in N2 and NH3, respectively, before nitridation. The enhanced nitridation process for powders milled in N2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…27,28 The function of high-energy milling as an intermediate step in the aforementioned processes is to increase the reactivity of reactants so that formation of compounds can be completed at lower temperatures and/or shorter times. 25,27 High-energy milling can bring about many changes to powders subject to the milling process, including refinement of particle sizes and crystallite sizes, 25,26 formation of amorphous phases, [3][4][5]29 an increase of the internal strain 6,18 and the specific heat, 8 generation of free radicals, unsaturated groups, and deformed bonds at the surface, 30 -32 changes in grain boundary energies, 7,8 storage of considerable enthalpies, 7,8 release of gases, 33 and localized temperature increases. 34 -37 Because of these changes the free energy of reactants and the reaction kinetics to form reaction products have been increased substantially.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The function of high-energy milling as an intermediate step in the aforementioned processes is to increase the reactivity of reactants so that formation of compounds can be completed at lower temperatures and/or shorter times. 25,27 High-energy milling can bring about many changes to powders subject to the milling process, including refinement of particle sizes and crystallite sizes, 25,26 formation of amorphous phases, [3][4][5]29 an increase of the internal strain 6,18 and the specific heat, 8 generation of free radicals, unsaturated groups, and deformed bonds at the surface, 30 -32 changes in grain boundary energies, 7,8 storage of considerable enthalpies, 7,8 release of gases, 33 and localized temperature increases. 34 -37 Because of these changes the free energy of reactants and the reaction kinetics to form reaction products have been increased substantially.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that high energy ball milling can also activate the surface of particles and increase their reactivity. [29][30][31][32][33] Thus, one may argue that high energy ball milling also leads to enhanced surface diffusion due to the activated surface. However, it is well known that mass transport through surface diffusion does not result in densification of a powder compact.…”
Section: Sintering Enhancement Via Nanostructured Powdermentioning
confidence: 99%
“…Furthermore, high-energy milling can be designed as an intermediate step to promote reactions that can be completed only at high temperatures. The synthesis of carbides, silicides, nitrides and borides by this processing has been investigated by many researchers [7][8][9][10][11]. As an example, Calka and Williams reported that TiN, AlN and WN powders were produced by milling the corresponding metal in a nitrogen atmosphere [12].…”
Section: Introductionmentioning
confidence: 99%